Eender en toch anders: Bilaterale Kongress : Historici van Nederland en Suid-Afrika Wassenaar 6-8 Julie 2000: Tweede Nederlands-Zuid-Afrikaans Historisch Congres - enkele indrukke (Historia, 2021)
Accounts for the Bilateral Conference on Historians of the Netherlands and South Africa held during July 2000 in Wassenaar. Explains the common history between the two countries. Shows the differences and similarities in the two countries' historical approaches.
Keywords: Wassenaar; Eender en Toch Anders Bilateral Conference Historians of the Netherlands and South Africa 2000; History